A peptidomic approach of meat protein degradation in a low-sodium fermented sausage model using autochthonous starter cultures - de Almeida, Marcio Aurélio (2018)
Fermented sausage technology is currently compromised in decreasing the addition of NaCl. Use of starter cultures with peptidogenic potential could be a valuable strategy that can mask or hide off flavors produced by the use of NaCl substituents. In the present work, the peptidogenic potential of four lactic acid bacteria species was evaluated in a low-sodium beaker sausage (BS) model. Using a peptidomic approach, a total of 86 low molecular weight (LMW) peptides were accurately identified, mostly derived from myofibrillar proteins, especially actin, which generated 53 peptides. The BS inoculated with L. curvatus CRL705 generated 56 LMW peptides, followed by Enterococcus (E.) mundtii CRL35 with 43 peptides. In addition, BS inoculated with Lactobacillus (L.) plantarum and with L. sakei produced higher amino acid amounts over time as compared to the rest of BS models, highlighting the importance of both, time and sample effect on the overall free amino acid generation. The presence of each LAB strain in BS models generated a unique profile of small peptides and amino acids that could serve as a distinctive biochemical trait to differentiate specific fermented products. According to these results, E. mundtii and L. sakei, which are compatible between them, are proposed as the most efficiently adapted to low-sodium conditions. The use of selected strains during the processing of low-sodium fermented sausages could have a positive effect on the production of small peptides and free amino acids.